Acoustics. Software for the calculation of sound outdoors. Recommendations for a quality assured implementation of the COMMISSION DIRECTIVE (EU) 2015/996 in software according to ISO 17534-1 Part 4, (20th November 2020) - British Standards Institution,
No abstract available